PENGARUH ENDORSER SELEBRITAS, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN MIE SEDAP WHITE CURRY (Studi Pada Konsumen Mie Sedap White Curry di Lingkungan Kampus Unisbank Semarang) - Destiyawan Rizki Nugroho, 13.05.51.0184; Rizal R, Alimuddin (Students Journal of Economic and Management, 2017)
The research had an intention to examine the influences of Â celebrity endorser, brand image, price perception of purchasing decision. Â The population of this research is the customer of white curry noodle product with the total sample of 100 correspondents that has been taken by purposive sampling technique.The research study of this final project proposes three hypothesis that been tested using linier regression with data processing program spss. Based on that statistical experimentation, I got a result that :celebrity endorser have positive and significant impact on purchasing decision, brand image have positive and significant impact on purchasing decision, price perception have positive and significant impact on purchasing decision . In conclusion should noodle product continue to improve and maintain celebrity endorser,brand image,price perception to keep customer believing and to be loyal customerDAFTAR PUSTAKAÂ Aaker, D. A. 1997. Manajemen Ekuitas Merek, Spektrum, Jakarta.Â Aaker.David.A. 1991. Managing Brand Equity; Capitalizing on the value of a brand name. The Free Press, New York. N.Y.Â AndiMuhammad Ismail,D,E,P,(2016).âAnalisis Pengaruh Citra Merek,Persepsi Terhadap Kualitas dan Harga Terhadap Keputusan Pembelian Terasi Puger ( Studi Kasus Konsumen Terasi Puger di Pasar Tanjung,Pasar Kepatihan dan Pasar Gebang Kabupaten Jember)â Jurnal Ilmiah Inovasi 1Aries,IvandanImam Ghozali.2006.âAkuntansiKeperilakuanâ.Semarang:Universitas Diponegoro.Â A.Shimp, Terence.2003.Periklanan Promosi.Erlangga : Jakarta.Â Asiani,W.,and E.Ruswanti.2014.Pengaruh Celebrity Endorser Dalam Iklan Freshcare Aromatherapy Terhadap Keputusan Pembelian Journal Management 9 (1):69-75.Â Ferdinan,C.E.,and R.Nugraheni.2013.Analisis Pengaruh Presepsi Harga Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Suzuki Journal of Management 2(2)Â Boyd â Walker â Larreche, 2000, Manajemen Pemasaran,Erlangga, Jakarta.Â Ghozali, Imam. (2008), Model Persamaan Struktural Konsep dan Aplikasi dengan Program Amos 16.0, Badan Penerbit UNDIP Semarang.Â Ghozali, Imam. (2011). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 19 (edisi kelima.)Semarang: Universitas Diponegoro.Â Husein Umar, 2005. Metode Penelitian. Jakarta : Salemba EmpatÂ Indriantoro, Nur., Bambang Supomo, 2009. Metodelogi Penelitian Bisnis Untuk Akuntansi dan Manajemen, Edisi Pertama.Yogyakarta :BPFE Yogyakarta.Â J. Setiadi, Nugroho, SE., MM., 2003, âPerilaku Konsumen Konsep danImplikasi untuk Strategi dan Penelitian Pemasaranâ. Jakarta: KencanaÂ Keller, Kevin Lane, 1993, âConseptualizing, Measuring, and Managing Customer-Based Brand Equality,âJournal of Marketing, (January), 1-22Â Kotler, Philip and Kevin Lane Keller,2006,Marketing Management, 12e.Pearson Prentice Hall, New JerseyÂ Kotler, philip& Keller, K.L. (2009). Manajemen Pemasaran. Edisi13.Jilid 1.Jakarta : ErlanggaÂ Kotler, Philip dan Kevin Lane Keller, 2008. Manajemen Pemasaran, Jilid 1, Penerbit Erlangga. Jakarta.Â Kotler, Philip dan Gary Armstrong,2001, Prinsip-prinsip Pemasaran, Jilid 1,Edisi Kedelapan, Jakarta,Erlangga.Â Kotler, Philip & Armstrong, Gary, (2008).Â Prinsip-Prinsip Pemasaran(12thÂ ed.).Jilid1.Jakarta: ErlanggaÂ McCracken, Grant (1989), âWho is the Celebrity Endorser? Cultural Foundations of the Endorsement Process,â Journal of Consumer Research, 16 (December), 310-321.Â Musay, Fransisca Paramitasari. (2013). Pengaruh Brand Image Terhadap Keputusan Pembelian (Survei Pada Konsumen KFC Kawi Malang). Skripsi Fakultas Ilmu Administrasi Universitas BrawijayaÂ Peter, J.Paul dan Jery, C.Olson. 2000. Consumer Behaviour, Perilaku Konsumen dan Strategi Pemasaran: alih bahasa Damos Sihombing.Jakarta: ErlanggaÂ Prof. Dr. Husaini Usman, M.Pd dan R. Purnomo Setiady Akbar,M.Pd.2006.Pengantar Statistikaâ.Jakarta:Bumi AksaraÂ Rao Purba, 2006, Measuring Consumer Perception Through Factor Analysis, The Aaian Manager (February- March).Â Shimp, Terence A. (2000). Periklanan Promosi. Jakarta: Penerbit ErlanggaShimp, T.A. (2010),Â  Advertising, promotion , & other aspects of Integrated Marketing Communication, 8th Edition, South-Western, Cengage Learning.Silvera, D.H. and Austad, B., (2004). Factors Predicting The Effectiveness of Celebrity Endorsement Advertisements, European Journal of Marketing, 38, 11/12, 1509-1526.Â Suciningtyas,W,(2012), â Pengaruh Brand Awareness,Brand Image,dan Media Communication Terhadap Keputusan Pembelian,âManagement Analysis Journal 1(1)Sugiyono.(2004). Metode Penelitian Bisnis. Alfabeta, CV.BandungÂ Sugiyono (2007), Metode Penelitian Bisnis, Penerbit Alfabeta, Bandung.Â Sugiyono.(2009). Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta.Â Surachman, (2008).Dasar-dasar Manajemen Merek. Malang: BayumediaPublishingÂ www.beritaliputan6.comwww.cikarangonline.comwww.doktersehat.comwww.indonesia-investments.comwww.instantnoodless.orgZeithaml,Â  V.Â  A.,Â  1988,Â  ConsumerÂ  PerceptionÂ  ofÂ  Price,Â  Quality,Â  andÂ  Value:Â  a Means-end Model and Synthesis of Evidence,Â  Journal of Marketing, 52, pp. 2-11.